2009
DOI: 10.1242/jeb.025395
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine accumulation and up-regulation of glutamine synthetase activity in the swamp eel,Monopterus albus(Zuiew), exposed to brackish water

Abstract: SUMMARYThe swamp eel, Monopterus albus, is an air-breathing teleost which typically lives in freshwater but can also be found in estuaries, where it has to deal with ambient salinity fluctuations. Unlike other teleosts, its gills are highly degenerate. Hence, it may have uncommon osmoregulatory adaptations, but no information is available on its osmoregulatory capacity and mechanisms at present. In this study M. albus was exposed to a 5 day progressive increase in salinity from freshwater (1‰) to brackish wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 74 publications
2
31
1
1
Order By: Relevance
“…Since P. motoro is akin to marine elasmobranchs, results obtained in this study may have implications that differ from those reported by Tok and colleagues (Tok et al, 2009) in the teleost, M. albus. In euryhaline freshwater or marine elasmobranchs, the OUC is the dominant pathway of urea production and GS is the key initial nitrogen-tapping enzyme for urea production via CPS III-based OUC.…”
Section: Gs Activity and Protein Abundance Were Up-regulated During Acontrasting
confidence: 89%
See 3 more Smart Citations
“…Since P. motoro is akin to marine elasmobranchs, results obtained in this study may have implications that differ from those reported by Tok and colleagues (Tok et al, 2009) in the teleost, M. albus. In euryhaline freshwater or marine elasmobranchs, the OUC is the dominant pathway of urea production and GS is the key initial nitrogen-tapping enzyme for urea production via CPS III-based OUC.…”
Section: Gs Activity and Protein Abundance Were Up-regulated During Acontrasting
confidence: 89%
“…Ammonia is also detoxified to glutamine through GS in vertebrate brains (Cooper and Plum, 1987), although increases in glutamine synthesis and GS activity in non-brain tissues are uncommon among vertebrates, except for several air-breathing fishes, which include M. albus (Tay et al, 2003;Ip et al, 2004b;Chew et al, 2005), Bostrychus sinensis (Ip et al, 2001a;Anderson et al, 2002), Oxyeleotris marmorata (Jow et al, 1999) and Misgurnus anguillicaudatus (Chew et al, 2001), exposed to terrestrial conditions or environmental ammonia. In contrast, Tok and colleagues (Tok et al, 2009) reported that acclimation to 25‰ water led to significant increases in GS activity and protein abundance in the liver of M. albus. In this study, we also demonstrated that GS activity and protein expression were upregulated in muscle and liver of P. motoro exposed to 15‰ water.…”
Section: Gs Activity and Protein Abundance Were Up-regulated During Amentioning
confidence: 86%
See 2 more Smart Citations
“…Ammonium is then assimilated into nitrogenous organic compounds by the concerted effort of two enzymes that compose the GS and glutamate synthetase cycle (Teixeira and Fidalgo, 2009). This process is a defense mechanism in fish and indicates high levels of GS content (Tok et al, 2009). The gene sequence of GS has been cloned in many species (Fucci et al, 1995;Lai et al, 2011;Tanguy et al, 2005;Trapido-Rosenthal et al, 1993).…”
Section: Introductionmentioning
confidence: 99%